Arah Penataan dan Pengembangan Konsep Waterfront City Pada Objek Wisata Pantai Soge Pacitan - Iqbal Abdul Aziz Zain (JOURNAL ECONOMICS AND STRATEGY, 2022)
Soge Beach is a tourist attraction that has many tourist attractions. However, the use of space in it is still not structured and neatly arranged. This causes a decrease in tourist attraction, the quality of natural resources and the existing ecosystem. The concept of a waterfront city is a concept of structuring a waterfront area that emphasizes the principle of sustainability. The purpose of this study is to provide an overview of the direction of the arrangement and development of the waterfront city concept at the Soge Pacitan Beach tourist attraction. The research method used is a qualitative descriptive method to explain, explain, describe, describe, and answer the problems at Soge Beach in more detail. The results obtained are the spatial arrangement of the Soge Beach waterfront directed at land use, building planning, circulation and parking, open space, pedestrian paths, supporting activities, marking and preservation and conservation. As for the development of the waterfront, it is directed towards infrastructure, architecture, facilities and tourism activities. With these results, it is hoped that it will have an impact on the new face of the Soge Beach tourism object so that it can encourage rapid economic growth.